IMPROVED TEACHING OF THE SUBJECT “THE INTERACTION OF RADIATION WITH SUBSTANCES” IN HIGHER MEDICAL EDUCATIONAL INSTITUTIONS MODEL - B. Z. Polvonov; E.Kh. Bozorov; B. S. Ruzimatova; M. Z. Khudoyberdieva (American Journals, 2023)
This in the article student’s competence from physics practical exercises based on information important was one how many pedagogical technologies and their application methods. This is provided in the article in this subject education process interactive technologies, virtual laboratories and other innovative approaches based on organization to grow methodology analysis is made. Also, in the article approaches based on students practical-procedural competence development efficiency discussion will be done.
Keywords: Problem-based learning, microscope, blood, erythrocyte, interference, biological sample, medical physics, medical technology, pedagogical activities, creative thinking, radiation safety, X-ray.